Failure Detection of Powertrain Components in Motor Vehicles Using Vibroacoustic Methods - KRISTON, Balázs József; JÁLICS, Károly (Archives of Acoustics, 2025)
Although noise and vibration measurements are widespread in the machine diagnostics, they are not used in the diagnostics of the powertrain of motor vehicles. Our research aims to investigate the possibilities, advantages, and drawbacks of using noise and vibration diagnostics performed for motor vehicles. In this paper, we attempt to use vibroacoustic signals from a motor vehicle for diagnostic purposes. Ordinary audible malfunctions, for example, misfiring in a passenger car, were artificially created. The differences between the normal and faulty operating conditions were examined to identify evidence of failure in the vibration signal. Primarily, evaluation through Fourier transformation was performed to provide a visual correlation between the fault and the vibration behavior of the car. Detailed conclusions from the measurements and future research plans are discussed.